Heterogeneity of Axenfeld–Rieger Syndrome: Molecular and Clinical Findings in Chinese Patients - Zhang, Youjia; Chen, Xueli; Wang, Li; Sun, Xinghuai; Chen, Yuhong (Frontiers in Genetics, 2021)
Axenfeld–Rieger Syndrome (ARS) is a rare disease with a wide spectrum of ocular and systemic manifestations. The genetic spectrum of Chinese patients with ARS and genotype-phenotype correlations have yet to be described. To explore the molecular and clinical features in Chinese patients, fifty-five patients clinically diagnosed with ARS from independent families were recruited. Complete ophthalmic examination and next generation sequencing of anterior segment dysgenesis associated genes were performed in all patients, and segregation in available relatives was verified using Sanger sequencing. Eighteen FOXC1 variants, thirteen PITX2 variants, and two gross deletions spanning FOXC1 were detected in 35 out of 55 (63.6%) patients. Twelve FOXC1 variants, 9 PITX2 variants, and two gross deletions were novel. There was a wide range of variability and severity in ocular and systemic manifestations displayed in our patients. Patients with FOXC1 variants were diagnosed at a younger age and had a lower prevalence of systemic manifestations than patients harboring PITX2 variants and those without variants. To our best knowledge, this is the largest study of Chinese patients with ARS to date. Our findings expand the genetic spectrum of ARS and reveal genotype-phenotype correlations in Chinese patients with ARS. Genetic and clinical heterogeneity were present in our patients. Awareness of the extensive characterization may aid in the clinical management and genetic counseling of patients with this rare disease.